Sarcoidosis mimicking seborrheic dermatitis: another case of Sherlockian Dermatology - César Bimbi (Our Dermatology Online, 2014)
Even tiny despicable skin signs may eventually unveil systemic illnesses enabling a prompt start of medication and better prognosis. Here, we present a case of a 28-year-old female patient who came to the office complaining of a "minor irritation" on the left eyebrow that was a discrete and asymptomatic 5mm infiltrated apple jelly coloured papule that had started 6 months earlier. Biopsy of a second similar lesion discovered on left forearm showed granulomatous features of sarcoidosis. Under subsequent systemic investigation, the presence of sarcoidosis in other organs was found to be positive as stage II pulmonary sarcoidosis, and also with reticulo-endothelial involvement manifested by enlarged mediastinal lymph nodes. This case highlights the skin as a mirror to internal multisystemic disease and also the importance of investigating even small and discrete lesions with care and in depth.